2022
DOI: 10.3390/nu14194199
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Hydroxygallic Acid Derivative, Zingibroside R1 and a Sterol Lipid as Potential Active Ingredients of Cuscuta chinensis Extract That Has Neuroprotective and Antioxidant Effects in Aged Caenorhabditis elegans

Abstract: We examined the effects of the extracts from two traditional Chinese medicine plants, Cuscuta chinensis and Eucommia ulmoides, on the healthspan of the model organism Caenorhabditis elegans. C. chinensis increased the short-term memory and the mechanosensory response of aged C. elegans. Furthermore, both extracts improved the resistance towards oxidative stress, and decreased the intracellular level of reactive oxygen species. Chemical analyses of the extracts revealed the presence of several bioactive compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 171 publications
0
4
0
Order By: Relevance
“…Compound 16 with molecular ion peak at m/z of 185 [M-H] − was tentatively identified as hydroxy gallic acid [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compound 16 with molecular ion peak at m/z of 185 [M-H] − was tentatively identified as hydroxy gallic acid [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both extracts improved the resistance towards oxidative stress, and decreased the intracellular level of ROS. 126 UPLC-Q-Exactive Orbitrap MS analysis allowed for metabolite identification and annotation. The authors also put efforts into unravelling the responsible single components.…”
Section: Multicomponent Mixtures From Natural Sources With Anti-aging...mentioning
confidence: 99%
“…110,123,124 The worm's locomotion gradually declines with age and is therefore a straightforward health span marker. The rate of body movement can be accessed with markers such as maximum bending amplitude, crawling speed on agar, [125][126][127] number of body bends during xed intervals of time or bending angle. 128 The locomotion of worms can also be measured at the cohort level.…”
Section: Elegans Assays Related To Healthy Agingmentioning
confidence: 99%
“…To the hydroxycinnamates, specific antioxidant activities have been assigned and a decrease in proinflammatory lysophasphatidyl choline production [40]. A very recent study has shown that hydroxygallic acid derivatives are responsible for enhanced stress resistance in C. elegans, and thus display neuroprotective functions [41].…”
Section: Friwaldskyanum Flowersmentioning
confidence: 99%